A comprehensive review on mutan (a mixed linkage of α-1-3 and α-1-6 glucans) from bacterial sources. Issue 2 (3rd July 2021) - Boddapati, Sirisha; Gummadi, Sathyanaryana N.
ABSTRACT: Mutan is an extracellular sticky polymer having α-1-3 and α-1-6 glycosidic linkages with a large diversity in molecular weights and structures depending on the source. These compounds are reported to be highly thermostable and also have potential physiochemical and biological applications. The main aim of this review is to provide an overview of glucosyltransferases and their role in mutan synthesis. The production strategies and structural properties of bacterial mutans are discussed with a goal to improve production efficiency. The physicochemical features, chemical modifications, potential industrial applications and future prospects are also discussed. According to data, mutan and its derivatives will play a larger role in medicinal sectors and as thermoplastics in the near future. Abbreviations: ABTS: 2, 2ʹ-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid; BHI: Brain heart infusion broth; 13 C (HSQC) NMR: Heteronuclear Single Quantum Coherence NMR; CBMs: Carbohydrate binding modules; DPPH: 2, 2-diphenyl-1-picrylhydrazyl; FTIR: Fourier-transform infrared spectroscopy; GC–MS: Gas chromatography-mass spectrometry; GPC: Gel permeation chromatography; Gtfs: Glucosyltransferases; 1 H (DQF-COSY): Double-quantum filtered correlation spectroscopy; HPAEC-PAD: High-performance anion exchange chromatography with pulsed amperometric detection; HPLC: High performance liquid chromatography; HPSEC-RI: High-performance size exclusive chromatography coupled with refractive index; HPSEC-MALLS: High-performance size exclusive chromatography with multi-angle laser light scattering detection; MALDI-TOF: Matrix-Assisted Laser Desorption/Ionization-Time of Flight mass spectrometry; Mw : Weight-average molecular weight; MWD: Molecular weight distribution; NMR: Nuclear magnetic resonance spectroscopy; TEM: Transmission electron microscopy; THB: Todd Hewitt Broth; TTY: Tryticase tryptose yeast extract broth.